1965
DOI: 10.1172/jci105232
|View full text |Cite
|
Sign up to set email alerts
|

The Pressure-Volume Relationship of the Normal Pulmonary Capillary Bed*

Abstract: In isolated lung preparations (1, 2) and in normal subjects (3, 4), acute pulmonary vascular congestion increases breath-holding diffusing capacity for carbon monoxide (DLco) by increasing the instantaneous volume of blood available for CO absorption (Vc). Conversely, in normal men, procedures that decrease pulmonary vascular pressure decrease DLco (4,5); yet, the pulmonary capillary bed of the lung chronically subjected to increased intravascular pressure is less able to decrease its volume in response to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The pulmonary veins account for most of the lung blood volume and the total compliance of the pulmonary circuit. The CHAPTER 28: RESPONSE TO STRESS: GRAVITY 1031 pulmonary capillaries are relatively noncompliant (72,86,360). Total pulmonary vascular compliance in the rabbit is -0.1 ml.mmHg-1.kg-1 body wt (86).…”
Section: Blood Volume and Distributionmentioning
confidence: 99%
“…The pulmonary veins account for most of the lung blood volume and the total compliance of the pulmonary circuit. The CHAPTER 28: RESPONSE TO STRESS: GRAVITY 1031 pulmonary capillaries are relatively noncompliant (72,86,360). Total pulmonary vascular compliance in the rabbit is -0.1 ml.mmHg-1.kg-1 body wt (86).…”
Section: Blood Volume and Distributionmentioning
confidence: 99%
“…It is generally agreed that the size of the pulmonary capillary bed, as measured with the technic of Roughton and Forster (63), is directly dependent on the level of the transmural pulmonary vascular pressure (15,64,65). In particular, it has recently been reported that elevation of the transmural pressure by infusion of dextran and epinephrine to anesthetized dogs raises the pulmonary capillary blood volume (66).…”
Section: Fig 3 A) the Pressure-volume Relationship In The Pulmonarymentioning
confidence: 99%
“…This hypothesis is supported by the suggestion of DALY et al (1965) that the increasing rate of DL induced by an increase in capillary blood volume is decreased more upon pulmonary capillary dilation than upon pulmonary capillary recruitment.…”
Section: Discussionmentioning
confidence: 59%